2020
DOI: 10.1111/ajad.13069
|View full text |Cite
|
Sign up to set email alerts
|

Method for Successfully Inducting Individuals Who Use Illicit Fentanyl Onto Buprenorphine/Naloxone

Abstract: Background and Objectives: Individuals exposed to fentanyl are at risk of precipitated withdrawal using typical buprenorphine/ naloxone induction procedures. Methods: This case series describes buprenorphine/naloxone inductions of four individuals who tested positive for fentanyl. Results: Buprenorphine-precipitated withdrawal was observed in two individuals who completed a conventional buprenorphine/ naloxone induction strategy. Two more individuals completed a revised buprenorphine/naloxone induction strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 18 publications
3
68
0
Order By: Relevance
“…One case series successfully initiated buprenorphine in patients using fentanyl by using multiple low doses (2 mg buprenorphine) after patients showed mild to moderate withdrawal. 61 The use of "microdosing" protocols is also emerging, using successive small doses of buprenorphine to slowly displace full agonists from the opioid receptor. 62 Traditionally, the standard of care includes monitoring adherence to buprenorphine with 63 64 although no evidence shows that drug testing improves clinical outcomes.…”
Section: Buprenorphinementioning
confidence: 99%
See 1 more Smart Citation
“…One case series successfully initiated buprenorphine in patients using fentanyl by using multiple low doses (2 mg buprenorphine) after patients showed mild to moderate withdrawal. 61 The use of "microdosing" protocols is also emerging, using successive small doses of buprenorphine to slowly displace full agonists from the opioid receptor. 62 Traditionally, the standard of care includes monitoring adherence to buprenorphine with 63 64 although no evidence shows that drug testing improves clinical outcomes.…”
Section: Buprenorphinementioning
confidence: 99%
“…Longer periods may be needed (up to 18-24 hours) for patients using fentanyl because of its lipophilicity. One case series successfully initiated buprenorphine in patients using fentanyl by using multiple low doses (2 mg buprenorphine) after patients showed mild to moderate withdrawal 61. The use of “microdosing” protocols is also emerging, using successive small doses of buprenorphine to slowly displace full agonists from the opioid receptor 62…”
Section: Treatmentmentioning
confidence: 99%
“…There is a significant OUD treatment gap in the United States and the majority of efforts to expand treatment have focused on buprenorphine-related innovations ( Jones et al, 2015 ). However, emerging data suggest that an increasing number of patients who are seeking treatment for OUD have been using heroin that has been adulterated with high levels of fentanyl ( Ochalek et al, 2019 ), and accumulating evidence suggests that recent fentanyl exposure makes induction onto buprenorphine extremely difficult ( Antoine et al, 2020 ), likely because illicit fentanyl exposure takes up to 2 weeks to be fully excreted ( Huhn et al, 2020 ). The net result is a growing number of reports that buprenorphine may not provide adequate withdrawal suppression for these patients ( Gryczynski et al, 2019 ; Silverstein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 If buprenorphine is initiated prior to withdrawal onset, it can displace residual opioids, causing an uncomfortable and sometimes severe acute withdrawal syndrome known as precipitated opioid withdrawal (POW). 3 POW has been defined…”
Section: Introductionmentioning
confidence: 99%
“…2 Multiple recently published reports from patients and providers suggest that POW can occur even after waiting the recommended amount of time in patients with a history of fentanyl use. 3,5 It has been proposed that this phenomenon may occur due to the high lipophilicity of fentanyl, resulting in a long tail of elimination after chronic use. 6 Despite fentanyl's therapeutic use as a short acting analgesic, one study showed that in patients with OUD and chronic fentanyl use, urinary metabolites of fentanyl could be detected 2-3 weeks after last use when hospitalized in a treatment program.…”
Section: Introductionmentioning
confidence: 99%